2010
DOI: 10.3390/ma3084252
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics in Two-Dimensional Supramolecular Systems Observed by STM

Abstract: Since the invention of scanning tunneling microscopy (STM), 2D supramolecular architectures have been observed under various experimental conditions. The construction of these architectures arises from the balance between interactions at the medium-solid interface. This review summarizes molecular motion observed in 2D-supramolecular structures on surfaces using nanospace resolution STM. The observation of molecular motion on surfaces provides a visual understanding of intermolecular interactions, which are th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 81 publications
0
47
0
Order By: Relevance
“…Due to the high reproducibility of this technique, it is easy to implement self-assembly materials in the development of large-scale devices. The molecular ordering is strongly dependent on the intraand intermolecular interactions, temperature, concentration, solvent and also the chemical/physical interactions with substrate ( [17] and the references in there). STM is the perfect tool to study all of these factors while monitoring the monolayer formation in real time through high resolution images.…”
Section: Molecular 2d Patterned Arraysmentioning
confidence: 99%
“…Due to the high reproducibility of this technique, it is easy to implement self-assembly materials in the development of large-scale devices. The molecular ordering is strongly dependent on the intraand intermolecular interactions, temperature, concentration, solvent and also the chemical/physical interactions with substrate ( [17] and the references in there). STM is the perfect tool to study all of these factors while monitoring the monolayer formation in real time through high resolution images.…”
Section: Molecular 2d Patterned Arraysmentioning
confidence: 99%
“…MM and MD simulations have been successfully applied to a wide range of systems. [14][15][16][22][23][24][25] These simulations, however, neglect the supernatant liquid phase and remain limited to the quantification of lattice energies. Moreover, both MD and Monte Carlo (MC) simulations are valuable tools for understanding monolayer formation and selection processes.…”
Section: Recentlymentioning
confidence: 99%
“…Moreover, both MD and Monte Carlo (MC) simulations are valuable tools for understanding monolayer formation and selection processes. [25][26][27][28][29] For MC appropriate modelling of the intermolecular interactions is crucial, since the outcome is extremely sensitive to simulation parameters. On the other hand, MD as an atomistic simulation technique, does not require mapping of the molecular building blocks onto a model, but sensitively depends on parameters of the underlying force field.…”
Section: Recentlymentioning
confidence: 99%
“…In addition, dynamic structural changes at the solid/liquid interface can be visualized in situ. 11,29,30 Although a number of investigators have focused on the 2D structural formation using tectons, few studies can be found on the fabrication and control of nanoarchitectures by isotropic van der Waals interactions and post-structural conversions. This focused review provides a brief overview of our recent progress related to the formation of 2D structures by tuning the alkyl chain length and their subsequent transformation by external stimuli, such as heat, metallation and ultraviolet (UV) light.…”
Section: Introductionmentioning
confidence: 99%